In vitro interactions between Armillaria species and potential biocontrol fungi - Keča Nenad (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2009)
Interaction between Armillaria species and seven other fungi were tested in vitro. Tree antagonistic (Trichoderma viride, Trichotecium roseum and Penicillium sp.) and four decaying (Hypholoma fasciculare¸ Hypholoma capnoides, Phlebiopsis gigantea, and Pleurotus ostreatus) fungi were chosen for this study. The best results were noted for Trichoderma viride, because fungus was able to kill both mycelia and rhizomorphs of Armillaria species, while Hypholoma spp. inhibited both growth of Armillaria colonies and rhizomorph production.